The development and control of an autonomous sailboat - Van Tonder, Johann Ruben (Stellenbosch : Stellenbosch University, 2025)
Van Tonder, J. R. 2025. The Development and Control of an Autonomous Sailboat. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9c93b973-edf6-4442-95f0-44e551d83ead